2005
DOI: 10.1074/jbc.m500982200
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for 14-3-3σ Functional Specificity*♦

Abstract: The 14-3-3 family of proteins includes seven isotypes in mammalian cells that play numerous diverse roles in intracellular signaling. Most 14-3-3 proteins form homodimers and mixed heterodimers between different isotypes, with overlapping roles in ligand binding. In contrast, one mammalian isoform, 14-3-3, expressed primarily in epithelial cells, appears to play a unique role in the cellular response to DNA damage and in human oncogenesis. The biological and structural basis for these 14-3-3-specific functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
241
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(257 citation statements)
references
References 38 publications
(25 reference statements)
12
241
0
4
Order By: Relevance
“…Comparative structural analyses of 14-3-3 isoforms suggested regions, including the surface formed by helices H8 and H9 (Fig. 3C), which presumably dictate ligand and dimerization preferences (44,55,56). Our results show that the RGS domain of RGS3 interacts with the less conserved regions of helices H6 and H8 outside the central channel of the 14-3-3 dimer (Figs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Comparative structural analyses of 14-3-3 isoforms suggested regions, including the surface formed by helices H8 and H9 (Fig. 3C), which presumably dictate ligand and dimerization preferences (44,55,56). Our results show that the RGS domain of RGS3 interacts with the less conserved regions of helices H6 and H8 outside the central channel of the 14-3-3 dimer (Figs.…”
Section: Discussionmentioning
confidence: 61%
“…Residues that are totally conserved among all human isoforms are colored in yellow. The black ellipses in panels B and C indicate the specificity region believed to be involved in protein-protein interactions and responsible for isoform-selective contacts (44,55,56).…”
Section: Biophysical Characterization Of the 14-3-3⅐prgs3 Proteinmentioning
confidence: 99%
“…Previous studies have shown that, apart from , several of the isoforms are able to form heterodimers (2,3). The presence of unique residues at the dimer interface provided a clear structural explanation for its homodimerization preference (38). Using an in vivo-based approach, Chaudhri et al (2) found that the isoform preferentially formed heterodimers with no observable homodimer formation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a number of three-dimensional structures of 14-3-3 isoforms have been determined and deposited in the Protein Data Bank (PDB; www.pdb.org): , in its apo form (35), as peptide complexes (14,17,18) and in complex with serotonin N-acetyltransferase (AANAT) (36); and in apo-and peptide-bound states (37,38). In addition, the structure of was published (39) but not deposited in the PDB.…”
mentioning
confidence: 99%
“…The atomic structure of 14-3-3 has been determined (4,17) to have an overall dimeric structure that resembles a flattened horseshoe (1). Each subunit of the dimer consists of nine ␣-helices.…”
mentioning
confidence: 99%